'An ardent lover of cities': Sonja Lyneham's contributions to urban planning practice. Issue 3 (3rd July 2020) - Freestone, Robert; Pullan, Nicola
ABSTRACT: Sonja Lyneham's planning career extended from the late-1960s to the mid-2010s, commencing as a junior member of the team formulating the 1971 City of Sydney Strategic Plan and evolving to direct major planning projects at state and national levels of government in Australia, the Asia-Pacific arena and Eastern Europe. The evolution of planning practice over the course of her career is reflected in diverse engagements, informed here by five main themes – gender, data, neo-liberalism, collaboration and infrastructure. Drawing on memoirs, interviews and extant documentation, the paper appraises Lyneham's life and career as a practitioner who brought a strong economic approach and personal commitment to progressive social change befitting the changing times.